High Soluble Thrombomodulin Is Associated with an Increased Risk of Major Bleeding during Treatment with Oral Anticoagulants: A Case–Cohort Study - Toorop, Myrthe M. A.; van Rein, Nienke; Cannegieter, Suzanne C.; van der Meer, Felix J. M.; Reitsma, Pieter H.; Lijfering, Willem M.; Bos, Mettine H. A. (Thrombosis and Haemostasis, 2020)
Background Major bleeding occurs in 1 to 3% of patients treated with oral anticoagulants per year. Biomarkers may help to identify high-risk patients. A proposed marker for major bleeding while using anticoagulants is soluble thrombomodulin (sTM).Methods Plasma was available from 16,570 patients of the BLEEDS cohort that consisted of patients who started treatment with vitamin K antagonists between 2012 and 2014. A case–cohort study was performed including all patients with a major bleed (n = 326) during follow-up and a random sample of individuals selected at baseline (n = 652). Plasma sTM levels were measured and stratified by percentiles. Patients were also categorized by international normalized ratio (INR). Adjusted hazard ratios (for age, sex, hypertension, and diabetes) with 95% confidence intervals (CIs) were estimated by means of Cox regression.Results Plasma sTM levels were available for 263 patients with a major bleed and 538 control subjects. sTM levels were dose-dependently associated with risk of major bleeding, with a 1.9-fold increased risk (95% CI: 1.1–3.1) for levels above the 85th percentile versus the <25th percentile. A high INR (≥4) in the presence of high (≥70th percentile) sTM levels was associated with a 7.1-fold (95% CI: 4.1–12.3) increased risk of major bleeding, corresponding with a bleeding rate of 14.1 per 100 patient-years.Conclusion High sTM levels at the start of treatment are associated with major bleeding during vitamin K antagonist treatment, particularly in the presence of a high INR.
Keywords: thrombomodulin; anticoagulants; hemorrhage